2014
DOI: 10.1111/ors.12110
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and morphological pattern of clefts in the craniofacial region seen in a sub‐Saharan tertiary hospital

Abstract: Aim: Clefts in the craniofacial region are one of the commonest congenital anomalies recorded in literature. The incidence varies globally with racial differences observed. In Nigeria, the evaluation of the absolute incidence of oral clefts is a challenge as births and deaths are not adequately registered. Especially lacking is the relative prevalence of rare craniofacial clefts to the more common cleft lip and palate anomaly. This study aims to document the pattern of distribution of craniofacial clefts, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Kalantar-Hormozi et al 17 in Iran reported an average of 8 patients with rare facial clefts per year. Number of rare facial clefts in Nigeria was 2.1 to 6.8 cases per year 18,19 . The largest report of the West was from the Netherlands where van der Elzen et al 20 reported a total of 123 patients in 40 years (2.1 cases per year).…”
Section: Discussionmentioning
confidence: 99%
“…Kalantar-Hormozi et al 17 in Iran reported an average of 8 patients with rare facial clefts per year. Number of rare facial clefts in Nigeria was 2.1 to 6.8 cases per year 18,19 . The largest report of the West was from the Netherlands where van der Elzen et al 20 reported a total of 123 patients in 40 years (2.1 cases per year).…”
Section: Discussionmentioning
confidence: 99%